2020
DOI: 10.1177/0733464820904564
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Antipsychotic Drug Use and Rehabilitation Outcome in Post-Acute Hip Fractured Patients: A Retrospective Cohort Study

Abstract: Antipsychotic (AP) use may lead to numerous side effects which may affect rehabilitation outcomes. A retrospective cohort study was carried out on 448 hip fractured patients admitted to a post-acute geriatric rehabilitation center. Functional improvement was measured by the Functional Independence Measure (FIM), motor FIM (mFIM), and mFIM effectiveness. A multiple linear regression model and regression analysis was used to evaluate the level of association between AP use and achievement of favorable functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“… 36 ) Furthermore, among those taking PIMs, patients using antipsychotics had lower ADL at admission and discharge, lower improvement in ADL with rehabilitation, and required longer rehabilitation times compared with those not taking antipsychotics. 106 ) These findings demonstrate that polypharmacy and PIMs may worsen ADL in older adults requiring rehabilitation.…”
Section: Pharmacotherapy and Rehabilitation Outcomesmentioning
confidence: 72%
See 1 more Smart Citation
“… 36 ) Furthermore, among those taking PIMs, patients using antipsychotics had lower ADL at admission and discharge, lower improvement in ADL with rehabilitation, and required longer rehabilitation times compared with those not taking antipsychotics. 106 ) These findings demonstrate that polypharmacy and PIMs may worsen ADL in older adults requiring rehabilitation.…”
Section: Pharmacotherapy and Rehabilitation Outcomesmentioning
confidence: 72%
“…Statins have been shown to have both positive and negative effects on the physical function of older adults. 106 , 107 , 108 ) Older patients taking allopurinol who underwent convalescent rehabilitation showed greater improvement in ADL than those not taking allopurinol. 109 ) A recent systematic review found that the use of SSRIs in stroke patients with anxiety and depression improved ADL independence, disability, and neurological impairment.…”
Section: Pharmacotherapy and Rehabilitation Outcomesmentioning
confidence: 97%